Pengabdian Masyarakat melalui Program KKN Berbasis Masjid di Desa Sumber Arum Sukaraja - Sri Lestari; Riyani Ermanti Lubis; Elvi Nurul Khasanah; Ahmad Mizari; Rahmad Febryanto; Beti Nursholeha; Devita Mahardilla; Heni Asmarita; Aprilawa Grasella; Kiki Agustiawan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Community service activities through the Community Empowerment Learning Real Work Lecture (KKN) program aim to increase Islamic-based knowledge and do not require the possibility of increasing the insight of the residents of Sumber Arum Village towards a superior Seluma district. This activity is in line with the principles of the Fatmawati Sukarno Bengkulu State Islamic University and provides students with learning and work experiences through community empowerment activities in Sumber Arum village, Sukaraja District, Seluma Regency, Bengkulu Province. The target group together with KKN students accompanied by field supervisors carry out KKN activities together. In this activity, students are required to interact and try to solve various problems that exist in society and look for potentials that can be explored or utilized so that it can become a sustainable activity